The impact of financial market frictions on trade flows, capital flows and economic development - Spiros Bougheas; Rod Falvey (Center for Economic Studies and ifo Institute (CESifo), 2011)
We introduce financial frictions in a two sector model of international trade with heterogeneous agents. The level of specialization in the economy (economic development) depends on the quality of financial institutions. Underdeveloped financial markets prohibit an economy to specialize in sectors where finance is important. Capital flows and international trade are complements when countries differ in the degree of development of their financial sectors. Capital flows to countries with more robust financial institutions which in turn allow their economies to develop sectors that are financially dependent.
Keywords: G21; G15; 330; trade flows; capital flows; financial frictions; economic development; Finanzmarkt; Markteffizienz; Außenwirtschaft; Kapitalmobilität; Wirtschaftswachstum; Theorie